Towards an understanding of position effect variegation. - Tartof, K.D.; Bishop, C.; Jones, M.; Hobbs, C.A.; Locke, J. (Developmental Genetics, 1989)
Most variegating position effects are a consequence of placing a euchromatic gene adjacent to alpha-heterochromatin. In such rearrangements, the affected locus is inactivated in some cells, but not others, thereby giving rise to a mosaic tissue of mutant and wild-type cells. A detailed examination of the molecular structure of three variegating white mottled mutations of Drosophila melanogaster, all of which are inversions of the X chromosome, reveals that their euchromatic breakpoints are clustered and located approximately 25 kb downstream of the white promoter and that the heterochromatic sequences to which the white locus is adjoined are transposons. An analysis of three revertants of the wm4 mutation, created by relocating white to another euchromatic site, demonstrates that they also carry some heterochromatically derived sequences with them upon restoration of the wild-type phenotype. This suggests that variegation is not controlled from a heterochromatic sequence immediately adjacent to the variegating gene but rather from some site more internal to the heterochromatic domain itself. As a consequence of this observation we have proposed a boundary model for understanding how heterochromatic domains may be formed. It has been recognized for many years that the phenotype of variegating position effects may be altered by the presence of trans-acting dominant mutations that act to either enhance or suppress variegation. Using P-element mutagenesis, we have induced and examined 12 dominant enhancers of variegation that represent four loci on the second and third chromosomes. Most of these mutations are cytologically visible duplications or deficiencies. They exert their dominant effects through changes in the copy number of wild-type genes and can be divided into two reciprocally acting classes. Class I modifiers are genes that act as enhancers of variegation when duplicated and as suppressors when mutated or deficient. Conversely, class II modifiers are genes that enhance when mutated or deleted and suppress when duplicated. The available data indicate that, in Drosophila, there are 20-30 loci capable of dominantly modifying variegation. Of these, most appear to be of the class I type whereas only two class II modifiers have been identified so far.(ABSTRACT TRUNCATED AT 400 WORDS)